Synthesis and characterization of (Bi0.2Sb0.8)2Te3 thermoelectric nanocomposites via melt spinning - Fan, Shufen (2009)
Bi2Te3-based alloys are the best thermoelectric materials for near room temperature applications. However, its dimensionless figure of merit, ZT, has remained at a modest value of ~1 for the past 50 years. ZT is expected to increase in nanocomposite materials by maintaining a high power factor, but at the same time reducing the thermal conductivity. High throughput and extreme cooling rate makes melt spinning an attractive process for the synthesis of nanostructured materials. In this work, a series of p-type (Bi0.2Sb0.8)2Te3 nanocomposites with 0, 10, 20, 40 and 100 weight percent (wt%) melt spun inclusions were prepared through a combination of melt spinning and hot pressing processes and their thermoelectric properties evaluated. The nanocomposites generally exhibit lower electrical conductivity and higher Seebeck coefficient as compared to the bulk ingot. A peak power factor of ~4.0 x 10-3Wm-1K-2 was obtained in the 10wt% nanocomposite which is attributed to the slight decrease in electrical conductivity and drastic increase in Seebeck coefficient. A predicted ZT of ~0.9 at room temperature is obtained for the 10wt% nanocomposite using referenced thermal conductivity values of the bulk Bi2Te3 obtained from the literature. It was envisaged that the actual ZT of the nanocomposite would be higher as the thermal conductivity of nanocomposite materials has been shown in the literature to be lower than bulk materials.